Digital Technologies in the Training of Future English Teachers in conditions of distance learning - Sarzhanova, G.B.; Abdrakhmanova, S.T.; Rakhimbayeva, B.T. (KU Publ., 2022)
This article reveals the problem of the use of digital educational technologies in foreign language teaching and presents the educational possibilities of using these technologies in the process of learning and teaching various aspects of foreign language. The teacher can use the digital environment and distance learning as part of the blended learning model or as the main form of learning if this is provided for by the curriculum of the educational institution. When using this form of teaching a foreign language, the undoubted advantage is the flexibility of the learning process, since to the extent that the skills and level of knowledge of the student are taken into account, it is possible to establish an individual approach and teaching methods, as well as the methods, time and duration of studying the material. The authors conducted an experiment among students and undergraduates of the Faculty of Foreign Languages to identify the relevance of the use of digital technologies in the conditions of distance education in higher education. The survey was conducted remotely using the survio.com website.
Қашықтықтан оқыту жағдайында болашақ ағылшын тілі мұғалімдерін даярлау кезіндегі сандық технологиялар
Цифровые технологии при подготовке будущих учителей английского языка в условиях дистанционного обучения
Keywords: digital technologies; foreign language; English teachers; distance learning; multimedia; Internet technologies; higher education; online learning; webinar